Initial Investigation for Potential Motivators to Achieve Sustainable Construction Safety and Health. (2015) - Chandra, Herry Pintardi
Abstract: The sustainable construction safety and health is an integral aspect of sustainable and green building efforts. Sustainable construction is defined as the creation and responsible management of a healthy built environment based on resource efficiency and ecological principles. Therefore, the important thing is to know the potential motivators to achieve sustainable construction safety and health. The aims of this paper are to investigate the potential motivators, to determine the important factors in successful sustainable construction safety and health, and to suggest the model of initial investigation for potential motivators due to sustainable construction safety and health. High potential motivators can be identified such as project organization, leadership, and company support. In addition, the elements of the sustainable construction safety and health can be measured by on-site renewable energy and optimized energy performance; construction waste management; stormwater quality control; heat-island effect roof, indoor chemical and pollutant source control and outdoor air delivery monitoring; controllability of system-lighting and daylight 75% of spaces. The data collected from the questionnaire survey carried out from contractors, Selection of the indicators is highly significant in the context of a true measure of the representative practices across the latent or unmeasured variables for use in Partial Least Square (PLS). The results of this research suggest that the relationship between potential motivators and sustainable construction safety and health in which standardized coefficient of 0.429 for project organization, 0.424 for leadership, and 0.317 for company support. Moreover, the potential motivators was found to have influence on sustainable construction safety and health with standardized coefficient of 0.567. The results also show that the sustainable construction safety and health has a significant indicator in term of on-site renewable energy and optimized energy performance for standardized coefficient of 0.796.